Desmistificando Práticas de Gestão Chinesas na Diáspora: Extensão de abordagens weberianas ou romantização da análise? - João Feijó (Cadernos de Estudos Africanos)
The interest of the media and academics around the success of Chinese entrepreneurs, particularly in Southeast Asia, has reanimated the analyses on management cultures. From the last quarter of the twentieth century, attention was drawn to the particularities of small and medium-sized Chinese enterprises formed in the diaspora, highlighting the role of networks of trust and familiarity in management processes. Throughout this reflection, we try to analyse the way culturalist traits or ethnicity have been recovered in the explanation of what became known as Chinese economic miracle. Finally, it is intended to alert to the risk of essentialism in these analyses, proposing that these are strategies of adaptation to unfavourable political and socio-economic contexts.